2002
DOI: 10.1097/00006842-200205000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Telecommunications Technology as an Aid to Family Caregivers of Persons With Dementia

Abstract: The results demonstrate how current information and communication technologies can be used to help caregivers meet the challenges of caregiving and improve the quality of life for caregivers. The potential benefit of this type of technology for health care providers is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 10 publications
1
76
0
2
Order By: Relevance
“…[166][167][168] Improvements in caregiver outcomes like depression and strain have been demonstrated in interventions involving technology. Caregivers also report they find the on-line resources useful and appreciate the ability to communicate with each other and health care professionals.…”
Section: Caregiver Interventionsmentioning
confidence: 99%
“…[166][167][168] Improvements in caregiver outcomes like depression and strain have been demonstrated in interventions involving technology. Caregivers also report they find the on-line resources useful and appreciate the ability to communicate with each other and health care professionals.…”
Section: Caregiver Interventionsmentioning
confidence: 99%
“…Examples include ComputerLink 13 , the REACH computer-integrated telephone system (CTIS 14 ); AlzOnline 15 , Caring for Others 16 and the DEM-DISC (DEMentia Digital Interactive Social Chart 17 ). These schemes usually include an online information resource related to dementia care and local services, which can be accessed using simple search tools [13][14][15]17 . Other schemes have used online question and answer forums or educational classes 13,15 .…”
Section: Abstract: Caregiver Dementia Technology Ict Grounded Thementioning
confidence: 99%
“…Other schemes have used online question and answer forums or educational classes 13,15 . Telephone conferencing has also been used to allow caregivers to discuss topics and share experiences 14,16 . These studies have shown positive outcomes, including improved decision confidence, self-efficacy, mood and stress [13][14][15][16] .…”
Section: Abstract: Caregiver Dementia Technology Ict Grounded Thementioning
confidence: 99%
See 2 more Smart Citations